The Design Of The Picture Story Book “AKU ANAK MANDIRI” As A Motivational Media For Special Need Children At Sumber Dharma Elementary School, Malang City - Yogi Pratama; Rahmat Kurniawan; Pujiyanto Pujiyanto (IC-ITECHS, 2022)
SLB Sumber Dharma Malang City is an educational institution for mild mentally retarded, physically handicapped, and autistic children. SDLB Sumber Dharma Malang city does not yet have teaching media with visuals regarding daily activities that are clear and appropriate for SDLB students. Through the development of the SDLB book media entitled "Aku Anak Mandiri" with the aim of learning visual narrative media as an effort to develop children's character. Using data collection qualitative methods of observation, interviews, and literature. The instrument in the development of this book is 5W+1H Analysis, while the design method used is Design Thinking. The implementation of the mentally retarded learning module competence A contains 3 chapters; Covering Hygiene, Eating and Drinking; and Dress, as standard SDLB material. The illustration is designed using the concept of an illustrated story with 3 main characters, namely Kevin, Putri, and Maruna as a representation of children with various ethnic, religious and racial backgrounds of the Indonesian people. The teaching material contains questions in the form of formative and multiple-choice tests as student assessments. The trial was carried out on two validators, namely DKV lecturers and SDLB Sumber Dharma teachers with an assessment of each aspect of the media and teaching materials. The results of the trial were considered appropriate with the suitability of picture story books as learning media for SDLB Sumber Dharma students.